Enhanced Chemodynamic Therapy and Chemotherapy via Delivery of a Dual Threat ArtePt and Iodo‐Click Reaction Mediated Glutathione Consumption. Issue 12 (22nd October 2021) - Jin, Qiao; Yan, Siqi; Hu, Hao; Jin, Long; Pan, Yuliang; Zhang, Jun; Huang, Jia; Xiao, Haihua; Cao, Peiguo
Abstract: Cisplatin has been used as standard regimen for hepatocellular carcinoma (HCC), but its therapeutic efficacy is greatly limited by the drug resistance. Cisplatin alone cannot achieve an ideal therapeutic outcome. Herein, a dual threat hybrid artemisinin platinum (ArtePt) is synthesized to combine chemodynamic therapy (CDT) with chemotherapy. On the one hand, artesunate can react with intracellular ferrous ion to generate reactive oxygen species (ROS) via Fenton reaction for CDT. On the other hand, cisplatin can target DNA for chemotherapy. However, GSH in cancer cells can effectively consume free radicals and detoxify cisplatin simultaneously, which compromised the efficacy of CDT and chemotherapy. Hence, an amphiphilic polymer with an iodine atom in the side chain is designed and encapsulated ArtePt to form NP(ArtePt). This iodine containing polymer NP(ArtePt) can effectively deplete intracellular GSH via an Iodo‐Click reaction, thereby enhancing the effect of CDT as well as chemotherapy. Thereafter, a patient‐derived xenograft model of hepatic carcinoma (PDX HCC ) is established to evaluate the therapeutic effect of NP(ArtePt), and a significant antitumor effect is achieved with NP(ArtePt). Overall, this study provides an effective strategy to combine CDT with chemotherapy to enhance the efficacy of cisplatin via Iodo‐Click reaction, opening a new avenue for the cancer treatment. Abstract : A dual‐threat hybrid ArtePt is synthesized and then encapsulated with iodine atom containing polymer to form a nanoparticle (NP(ArtePt)). The obtained NP(ArtePt) can effectively deplete intracellular glutathione in cancer cells via an Iodo‐Click reaction, and combine chemodynamic therapy with chemotherapy. Excellent antitumor effect is achieved on a patient‐derived xenograft model of hepatocellular carcinoma, opening a new avenue for the cancer treatment.